Pengaruh Monosodium Glutamat Terhadap Fertilitas Pria - Ika Inda Bani; Zulkarnain Zulkarnain; Gholib Gholib (Fakultas Kedokteran Universitas Riau, 2023)
The current modern era causes lifestyle changes, especially in urban communities, in terms of daily consumption patterns that tend to be accustomed to consuming fast food that contains many additional compounds. A compound commonly known as a food flavoring additive is monosodium glutamate (MSG), a sodium salt that is naturally produced from L-glutamic acid. Apart from its role in enhancing the taste of food, several studies have shown that MSG has toxic effects on human and animal tissues including the reproductive system which may cause infertility. Glutamate in MSG has a direct reaction effect at the cellular level, one of which forms free radicals and causes oxidative stress. The increase in free radicals in the body can cause damage to the organs of the body including the testes. Damage caused by MSG can also occur centrally in the hypothalamus so that it interferes with the hormonal and endocrine reproductive systems. Damage to pituitary cells will inhibit the production of gonadotropin-releasing hormone (GnRH), resulting in a decrease in gonadotropin levels, either luteinizing hormone (LH) or follicle stimulating hormone (FSH) produced by the pituitary gland. This article aims to discuss in detail how MSG affects male fertility.